2016
DOI: 10.4269/ajtmh.15-0797
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Hepatitis B Transmission Risks Among Health Workers in Tanzania

Abstract: Abstract. Healthcare workers are at increased risk of contracting hepatitis B virus (HBV), particularly in settings of high HBV seroprevalence, such as sub-Saharan Africa. We evaluated HBV knowledge among health-care workers in rural Tanzania by distributing an HBV paper survey in two northern Tanzanian hospitals. There were 114 participants (mean age 33 years, 67% female). Of the participants, 91% were unaware of their HBV status and 89% indicated they had never received an HBV vaccine, with lack of vaccine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
4
16
3
Order By: Relevance
“…None of the infected HCWs were aware of their infection status [ 29 ]. This finding is similar to the one observed in Arusha, where >90% of HCWs in two teaching hospitals were reported not to be aware of their HBV statuses [ 35 ].…”
Section: Epidemiologysupporting
confidence: 88%
See 1 more Smart Citation
“…None of the infected HCWs were aware of their infection status [ 29 ]. This finding is similar to the one observed in Arusha, where >90% of HCWs in two teaching hospitals were reported not to be aware of their HBV statuses [ 35 ].…”
Section: Epidemiologysupporting
confidence: 88%
“…Of these, 23% were unable to mount the immunity (anti-HBs titre < 10 ml/U), leaving them in a risk of acquiring HBV infection [ 29 ]. The same trend has also been observed in Arusha where 89% of HCWs reported not to have received any HBV vaccine, the main reason being unawareness of the vaccine [ 35 ].…”
Section: Preventionsupporting
confidence: 67%
“…In another study Epidemiological data for Hepatitis B in Africa contrary to our findings carried out in Tanzania to assess Knowledge of Hepatitis B Transmission Risks Among Health Workers where 114 participants (mean age 33 years, 67% female) were involved, 91% were unaware of their HBV status and 89% indicated they had never received an HBV vaccine, with lack of vaccine awareness being the most common reason (34%) [21].…”
Section: Knowledge Of Health Workers On Hepatitis Bcontrasting
confidence: 63%
“…Previous studies from Tanzania and Rwanda have found poor HBV screening and vaccination uptake among health-care workers despite them knowing that working in health-care settings increases their risk to acquire HBV. 21,29 In our population, the natural history of HBV infection as well as its clinical complications were relatively well mastered, potentially explaining the good self-reported practices of personal HBV screening and vaccination. Nevertheless, more education about the drastic effects of the virus is needed in health-care settings throughout sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 89%